1999
DOI: 10.1099/00221287-145-12-3399
|View full text |Cite
|
Sign up to set email alerts
|

S-layer protein production by Corynebacterium strains is dependent on the carbon source

Abstract: Three strains of Corynebacterium producing various amounts of PS2 S-layer protein were studied. For all strains, more PS2 was produced if the bacteria were grown in minimal medium supplemented with lactate than if they were grown in minimal medium supplemented with glucose. The consumption of substrate and PS2 production was studied in cultures with mixed carbon sources. It was found that the inhibitory effect of glucose consumption was stronger than the stimulatory effect of lactate in one strain, but not in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Furthermore, real-time RT-PCR revealed that cg2831 and the cspB gene were expressed at higher rates during exponential growth than during stationary phase. In earlier studies, Soual-Hoebeke et al (1999) have demonstrated that the amount of S-layer protein is dependent on the growth phase of C. glutamicum and is related to the environmental stimulus of the carbon source available within the growth medium. For instance, the use of lactate as carbon source results in an enhanced formation of the S-layer, and, as a consequence thereof, C. glutamicum cells are densely covered by an ordered S-layer lattice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, real-time RT-PCR revealed that cg2831 and the cspB gene were expressed at higher rates during exponential growth than during stationary phase. In earlier studies, Soual-Hoebeke et al (1999) have demonstrated that the amount of S-layer protein is dependent on the growth phase of C. glutamicum and is related to the environmental stimulus of the carbon source available within the growth medium. For instance, the use of lactate as carbon source results in an enhanced formation of the S-layer, and, as a consequence thereof, C. glutamicum cells are densely covered by an ordered S-layer lattice.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have demonstrated that the amount of S-layer protein synthesized by C. glutamicum is dependent on the carbon source of the growth medium (Soual-Hoebeke et al, 1999). In particular, the addition of lactate to the growth medium has a stimulatory effect on PS2 production as well as on S-layer formation, whereas an inhibitory effect on PS2 synthesis is observed when glucose is used as carbon source.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The promoterprobe vector pMF2 (Soual-Hoebeke et al, 1999) was used for construction of transcriptional fusions of the ldh promoter region or of the sugR-cg2116 promoter region and the promoterless lacZ gene. Plasmid pMF2 was first digested with EcoRI and BamHI and purified.…”
mentioning
confidence: 99%